Transformation of an institution: The development of San Lazaro Hospital as a contagious diseases hospital under American administration, 1898-1918 - Taguba, Phillip Daniele D.C. (Animo Repository, 2022)
This study is about the development of San Lazaro Hospital during the American colonial period from 1898 to 1918. Fr. Juan Clemente established the hospital in 1578, and its rich history with the Franciscans endured for three centuries until the Americans took over in 1898. In analyzing this critical point in the hospital’s history, the study utilizes the new institutionalism theoretical framework and a descriptive-analytical method to analyze the hospital’s role from 1898 to 1918. The Americans implemented an all-new policy on public health, causing cautious Filipinos to have conflicts in following the new mandates of the newly arrived colonizers. Despite the cultural opposition, the Board of Health, through San Lazaro Hospital, utilized their medical knowledge to implement sanitation and modern medical practices in the disease-ridden Manila. Facing the inadequacies of the hospital from the previous 1902 cholera epidemic, the San Lazaro Hospital received improvements, and it became a sophisticated contagious diseases hospital in the country that treated contagious diseases such as cholera, smallpox, plague, and tuberculosis. In addition, the hospital also served as a leper and insane hospital. San Lazaro Hospital is mainly managed by the Americans and has established itself as a defining medical institution until the hospital was eventually handed over to Filipino administrators during the Filipinization movement in 1918.